(untitled) (Research, Society and Development, 2022)
The objective of this study was to verify the effect of kinesio-taping (KT) application of the origin for muscle insertion (O>I) and insertion for muscle origin (I>O) in healthy participants, through surface electromyography and peak torque of gastrocnemius muscles. A total of 69 participants with an average age of 22.9±5.2 years were evaluated, 41 women with an average age of 22.0±5.1 years, BMI 25.1±4.6 kg/m2, and 28 men with an average age of 22.0±5.1 years, BMI 23.1±3.3 kg/m2, randomized under three conditions: O>I, I>O and no KT (control), repeated three times with five-minute rest between sessions. The peak torque of the gastrocnemius lateral (GML) and medial (GMM) muscles was evaluated at speeds 30º/s 60º/s 120º/s and muscle activity through surface electromyography. Repeated-measurement ANOVA showed effect only on the variable speed (F=767,1; p<0.001) and the variables condition (F=0.010; p=0.990) and interaction (F=0.199; p=0.892) were not significant. In electromyography, Root mean Square (RMS) did not differ in the conditions evaluated, presenting standard behavior without significant differences. The KT application regardless of being O>I or I>O muscular, did not alter the muscle recruitment or contribute to the increase in peak torque performance during the three speeds.